2021
DOI: 10.31557/apjcp.2021.22.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Polymorphisms of miR-1307, miR- 1269, miR-3117 and Breast Cancer Risk in a Sample of South East Iranian Women

Abstract: Introduction: MicroRNAs (miRNAs) play an essential role in the susceptibility and development of cancer cells. Objective: Examining the dependency of breast cancer risk with genetic polymorphisms of miR-1307, miR-1269, and miR-3117 in a sample of Iranian women (southeast region). Methods: The case-control study consisted of 520 individuals (260 diagnosed BC patients, 260 healthy individuals). The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used for genotyping of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Abnormal expression of miRNA causes abnormal transcription and expression of its target genes, which provides important conditions for the occurrence and metastasis of malignant tumors [ 9 ]. With the continuous development of molecular biology technology in recent years, studies have found that a variety of miRNAs are abnormally expressed in cervical cancer [ 10 ], breast cancer [ 11 ], bladder cancer [ 12 ], and other malignant tumors, making miRNAs become new targets for targeted therapy of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of miRNA causes abnormal transcription and expression of its target genes, which provides important conditions for the occurrence and metastasis of malignant tumors [ 9 ]. With the continuous development of molecular biology technology in recent years, studies have found that a variety of miRNAs are abnormally expressed in cervical cancer [ 10 ], breast cancer [ 11 ], bladder cancer [ 12 ], and other malignant tumors, making miRNAs become new targets for targeted therapy of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For the miR-3117 gene, the following sequences were identi ed: rs7512692-F: 5'-TGG CAG TTG CTG GTA CTC TT-3' and rs7512692-R: 5'-CTCAAGTCTCCTCCCCCATC-3'. for the variant rs4655646-F: 5´ TGG CAT GTG AGG AAA GTT GGA-3´ and rs4655646-R: 5´ AGATATTGGGCCTCTACCCGT-3´ [30].…”
Section: Genotypingmentioning
confidence: 99%
“…Five microliters of each PCR product were subjected to digestion with 5U of the following restriction enzymes: The HOTAIR rs920778 (MspI) and miR-3117 rs7512692 (Hpy1881II) and rs4655646 (TaqI) (New England Biolabs, USA) were digested according to the manufacturer's instructions and separated in a 6% polyacrylamide gel. Genotypes were identi ed according to the methods described by Kashani et al ( 2021) and Sarabandi et al (2021). To ensure the quality of the genotyping processes, approximately 10% of the randomly selected samples were reprocessed, and the results were found to be 100% consistent.…”
Section: Genotypingmentioning
confidence: 99%
“…rs73239138 is a single nucleotide polymorphism located in the sequence of miR-1269a. miR-1269a rs73239138 is also associated with a reduced risk of breast cancer among women in southeastern Iran (Sarabandi et al, 2021). In gastric cancer and liver cancer cells, overexpressed miR-1269a can inhibit the apoptosis of gastric cancer cells.…”
Section: The Mechanism Of Mir-1269 Variants In Tumormentioning
confidence: 99%